2005
DOI: 10.1179/crn.2005.008
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Condyle Fossa Relationships on Head Posture

Abstract: Although it is commonly accepted that there is an interrelationship between the temporomandibular joint (TMJ) and head posture, few, if any, previous studies have quantified this effect. The purpose of this study is to quantify the effect of a change in the condyle fossa relationship of symptomatic temporomandibular joints on head posture. Charts of 51 patients (N=10 men and N=41 women) with symptomatic TMJ pathology were reviewed. The condyle fossa relationships were measured pre- and posttreatment using sagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 8 publications
0
16
0
5
Order By: Relevance
“…Patients with TMD show greater changes in the body’s center of gravity 25. Several studies have shown that patients with TMD present an excessively forward head position,26,27 usually associated with the shortening of the posterior cervical extensor muscles (suboccipital, semispinalis, splenii, and upper trapezius muscles), as well as shortening of the SCM 28. Anterior displacement of the head lowers the field of vision and, in the attempt to improve the field of vision, cervical lordosis increases 29,30.…”
Section: Stomatognathic System and Body Posturementioning
confidence: 99%
“…Patients with TMD show greater changes in the body’s center of gravity 25. Several studies have shown that patients with TMD present an excessively forward head position,26,27 usually associated with the shortening of the posterior cervical extensor muscles (suboccipital, semispinalis, splenii, and upper trapezius muscles), as well as shortening of the SCM 28. Anterior displacement of the head lowers the field of vision and, in the attempt to improve the field of vision, cervical lordosis increases 29,30.…”
Section: Stomatognathic System and Body Posturementioning
confidence: 99%
“…It has been demonstrated that changes in neck posture can lead to changes in the biomechanics of the temporomandibular joint, affecting the function of the stomatognathic system and leading to the development of temporomandibular joint dysfunction (TMD) 5,6 . A recent study showed that the prevalence of TMD in the elderly population with PD is 23.08% reaching women more frequently 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Changes in mandibular position are induced by variations in body posture, subsequently affecting the condylar position and the tension of the muscles supporting the mandible 36 . Therefore, previous studies have shown how patients with TMD presented with anteriorly positioned heads 37,38 and also how postural changes in the cervical region can cause TMD 39 .…”
Section: Discussionmentioning
confidence: 99%